Peningkatan Kinerja Pelaku Industri Rumah Tangga Kreatif Melalui Kemampuan Inovasi Dan Branding Produk Literasi Melalui Teknologi Dan Pengenalan Peluang Bisnis - Palupi, Fitria Hayu; Noviati, Titik Dwi; Ribhi, Ahmad Aufar (Jurnal Abdi Mas Adzkia, 2023)
The biggest problems faced by home industry players are difficulties in marketing products and lack of skills in using technology as well as a lack of product quality assurance which causes difficulties in accessing a wider market. The aim of this service is to improve the performance of creative home industry players through innovation capabilities and product branding through technological literacy and recognition of business opportunities. The method used in this service starts from the planning process, implementing activities and monitoring evaluation. In the process of implementing activities in the form of providing training using lecture and discussion methods as well as mentoring to participants. This program was carried out by a team of ITSK Lecturers and Students Sugeng Hartono with the target being household food industry players who are members of ASEMKESUR in Solo Raya. The results of this program are that household food industry players obtain a PIRT licensing certificate as a quality guarantee for business products and use digital platforms to support the progress of their business.Keywords: Bookkeeping System, Micro Small And Medium Enterprises, PIRT     Licensing